Analysis of ERS wind scatterometer time series over Sahel (Mali) - Jarlan, L.; Mougin, E.; Frison, P.L.; Mazzega, P.; Hiernaux, Pierre H.Y. (Elsevier, 2002)
ERS wind scatterometer (WSC) time series are analyzed over different ecoclimatic regions of the African Sahel during the period 1991–1995. At 45° incidence angle, the strong seasonality of o time series can be directly linked to the successive wet and dry seasons. Moreover, the annual o dynamic range was found to be strongly correlated to total rainfall. The interpretation of the o temporal plots is carried out by combining a backscattering model to a grassland growth model. Results highlight the decreasing contribution of the herbaceous component with latitude. However, its contribution is far from negligible and can reach 60% in the Soudano-Sahelian subzone at peak herbaceous mass. Additionally, the tree layer has a negligible effect on the radar signal at the scale of a resolution cell. Finally, a simple parametric backscattering model is calibrated and used in an inversion process. The resolution of the inverse problem is based on a `brute-force' method that consists of exploring all the combinations of parameters of interest. Despite a poor estimation of the temporal variation of the herbaceous mass Bt, the retrieved maximum mass compares well with ground estimates.